Respon Streptococcus pneumonia Terhadap Senyawa Fitokimia Ekstrak Etanol dan n-Heksan Daun Salam (Syzygium polyanthum Wight) - Sesilia Rante Pakadang; Nur Hikmah Hasrul; St Ratnah; Alfrida Monica Salasa; Djuniasti Karim; Andi Muhammad Farid; Asmawati Asmawati (Media Farmasi XXX, 2022)
Response Of Streptococcus pneumonia To Photochemical Compounds Of Ethanol and n-Hexane Extract Of Salam Leaf (Syzygium polyanthum Wight)Pneumonia due to pneumococcal bacteria is generally caused by Streptococcus pneumonia. Pneumonia cases in Indonesia in 2019 reached 400 thousand and increased due to the impact of Covid-19 on children. The response of bacteria to chemical compounds is scientific proof of the antibacterial properties of a plant extract that is polar or non-polar based on the type of solvent used in the extraction process. Method. Identification of active compounds in extracts based on phytochemical screening. The antibacterial potential was determined based on the ability of the active compound to inhibit the growth of Streptococcus pneumoniae by agar diffusion. The test materials were ethanol extract and n-hexane of salam leaf (Syzygium polyanthum Wight). The results showed that the ethanol extract contained alkaloids, phenols, tannins, flavonoids, glycosides, saponins, and phlobatanins. Hexane extract contains alkaloids, glycosides, and saponins. It was concluded that Streptococcus pneumonia responded to ethanol extract of salam leaves and cephalosporins but did not respond to hexane extract from salam leaves. Ethanol extracts 1,3 and 5% were bacteriostatic but hexane extracts with the same concentration did not inhibit the growth of Streptococcus pneumonia.Keywords:  Syzygium polyanthum Wight; Antibacteria;, Streptococcus pneumoniaePneumonia akibat bakteri pneumokokus umumnya disebabkan oleh Streptococcus pneumoniae. Kasus pneumonia di Indonesia tahun 2019 mencapai 400 ribu dan  meningkat akibat dampak Covid-19 pada anak. Respon bakteri terhadap senyawa kimia adalah pembuktian ilmiah sifat antibakteri dari suatu ekstrak tanaman yang bersifat polar atau non polar berdasarkan jenis pelarut yang digunakan dalam proses ekstraksi. Metode. Identifikasi senyawa aktif dalam ekstrak berdasarkan skrining fitokimia. Potensi antibakteri ditentukan berdasarkan kemampuan senyawa aktif menghambat pertumbuhan Streptococcus pneumoniae secara difusi agar. Bahan uji ekstrak etanol dan n-heksan daun salam (Syzygium polyanthum Wight). Hasil penelitian menunjukkan ekstrak etanol 96% mengandung alkaloid, fenol, tannin, flavonoid, glikosida, saponin dan phlobatanin. Ekstrak heksan mengandung alkaloid, glikosida dan saponin. Disimpulkan  Streptococcus pneumoniae memberikan respon terhadap ekstrak etanol daun salam dan cefalosforin  namun tidak memberikan respon terhadap ekstrak heksan daun salam.  Ekstrak etanol 1,3 dan 5% bersifat bakteriostatik namun ekstrak heksan dengan konsentrasi yang sama tidak menghambat pertumbuhan Streptococcus pneumoniae.Kata kunci :  Syzygium polyanthum Wight; Antibakteri;  Streptococcus pneumoniae